Linking social media usage and SME's sustainable performance: The role of digital leadership and innovation capabilities. (February 2022) - Borah, Prasad Siba; Iqbal, Shuja; Akhtar, Shamim
Abstract: The increasing use of social media and its ability to aid small and medium-sized enterprises (SMEs) to target large audiences at once has triggered to transformation in how SMEs perform their routine operations. Research on social media usage and SME performance is comparatively novel and patchy; yet, researchers, managers, and policymakers have limited interest in investigating the construct specifically in developing countries. This study explores the relationships between social media usage and innovation capabilities to improve sustainable SME performance. This study grounded the theoretical model building on a resource-based view. An online questionnaire was administered to gather data and was further analyzed quantitatively. The proposed interlinks were assessed using a sample of 549 employees of SMEs using SmartPLS techniques. The results show that social media usage has a positive and significant direct influence on innovation capabilities and sustainable SMEs performance, and innovation capabilities also have a positive and significant direct impact on sustainable SME performance. In addition, findings reveal that social media usage can enhance sustainable SME performance when mediated by innovation capabilities and moderated by digital leadership. This study offers several theoretical and practical implications. Highlights: The increasing use of social media's ability to lead SMEs to target large audiences has triggered to transformation in how SMEs perform their routine operations. This study fills the limited interest in investigating the construct specifically in developing countries. Social media usage can enhance sustainable SME performance when mediated by innovation capabilities and moderated by digital leadership. This study offers several theoretical and practical implications for SMEs and relevant policy makers.